2020
DOI: 10.3389/fgene.2020.591806
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Circular RNAs in Response to Low-Temperature Stress in Tomato Leaves

Abstract: Abiotic stress adversely inhibits the growth and development of plants, by changing the expression of multiple genes. Circular RNAs (circRNAs), as a class of non-coding RNAs, function in transcriptional and posttranscriptional regulation. Yet, the involvement of circRNAs in abiotic stress response is rarely reported. In this study, the participation and function of circRNAs in low-temperature (LT)-induced stress response were investigated in tomato leaves. We generated genome-wide profiles of circRNAs and mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Most circRNAs have been reported to regulate plant growth, development, and stress responses. For example, under a low-temperature treatment, 1759 circRNAs were induced in tomato leaves [ 52 ]. In maize, a total of 24 and 22 DECs obtained from the leaves and roots, respectively, were responsive to deficient nitrogen stress [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most circRNAs have been reported to regulate plant growth, development, and stress responses. For example, under a low-temperature treatment, 1759 circRNAs were induced in tomato leaves [ 52 ]. In maize, a total of 24 and 22 DECs obtained from the leaves and roots, respectively, were responsive to deficient nitrogen stress [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…It then filtered the candidate circRNAs based on the global comparison, the reads support of circRNAs, and the annotation information to identify junction reads. Those with a read number larger than two were selected as the identified circRNA ( Gao et al., 2015 ; Ye et al., 2015 ; Tong et al., 2018 ; Zhang et al., 2019 ; Li et al., 2020 ; Philips et al., 2020 ; Yang et al., 2020 ; Jiang et al., 2021 ). The results that appeared in both find_circ and CIRI2 were selected as candidate circRNAs ( Xu et al., 2018 ; Liu et al., 2019 ; Li et al., 2020 ; Philips et al., 2020 ; Yang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Those with a read number larger than two were selected as the identified circRNA ( Gao et al., 2015 ; Ye et al., 2015 ; Tong et al., 2018 ; Zhang et al., 2019 ; Li et al., 2020 ; Philips et al., 2020 ; Yang et al., 2020 ; Jiang et al., 2021 ). The results that appeared in both find_circ and CIRI2 were selected as candidate circRNAs ( Xu et al., 2018 ; Liu et al., 2019 ; Li et al., 2020 ; Philips et al., 2020 ; Yang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, overexpression of the grape Vv-circATS1 , a circRNA derived from grape glycerol-3-Pacyltransferase gene, improved the cold tolerance of transgenic Arabidopsis plants [ 16 ]. To investigate the function of circRNAs in tomato leaves’ response to low-temperature stress, Yang et al identified 1759 low-temperature-induced circRNAs, and revealed that 383 differentially expressed circRNAs and their parental genes were functionally enriched in the regulation of metabolism, signal transduction, and environment adaptation pathways, revealing the vital roles of circRNA and its corresponding parental genes in response to low-temperature stress [ 22 ]. These studies demonstrated that circRNAs possess the abilities to respond to biotic and abiotic stresses by regulating the expression of stress-related genes.…”
Section: Introductionmentioning
confidence: 99%